Analysis of BOD and COD levels for home industry wastewater: A case study in a sewage streams - Nelius Harefa; Arifman Gulo; Saronom Silaban (Pascasarjana Universitas Negeri Medan, 2021)
Environmental pollution caused by waste is pollution that very dangerous for living things. In particular, water pollution, waste that is disposed of through waterways will disrupt the water ecosystem which will have an impact on human life. On the other hand, the development of entrepreneurship such as home industry has a positive impact on society, especially in terms of the economy. Therefore, water pollution indicators are needed that can be used as guidelines in treating wastes such as BOD and COD. In this study, analyzed the levels of BOD and COD from home industry wastewater in the Cawang area. The home industry includes laundry, cracker business, restaurants, printing houses, photocopying, and snack businesses. Based on the results of data analysis, the highest BOD level was 45.827 in samples taken at night. And, the highest COD levels were 95.923 in samples taken at night. These data indicate that the levels of BOD and COD in the water in the home industry waste disposal sites are below the standard threshold for wastewater quality. The levels of BOD and COD are in the safe category for aquatic biota.Keywords: BOD levels, COD levels, Waste, Water pollution